Bioactive 1, 2, 3‐Triazoles: An Account on their Synthesis, Structural Diversity and Biological Applications. Issue 10 (11th February 2021) - da S. M. Forezi, Luana; Lima, Carolina G. S.; Amaral, Adriane A. P.; Ferreira, Patricia G.; de Souza, Maria Cecília B. V.; Cunha, Anna C.; de C. da Silva, Fernando; Ferreira, Vitor F.
Abstract: The triazole heterocycle is a privileged scaffold in medicinal chemistry, since its structure is present in a large number of biologically active molecules, including several drugs currently in the market. Due to their vast applications, a wide variety of methods are described for their preparation, such as the 1, 3‐dipolar cycloaddition and processes involving diazo compounds and diazo transfer reactions. Considering the significant number of contributions from our research group to this chemistry in recent decades, in this account we discuss both the development of new methods for the synthesis of 1, 2, 3‐triazoles and the preparation of new triazole‐functionalized biologically active molecules using classical approaches. Abstract : This review paper discusses both the development of new methods for the synthesis of 1, 2, 3‐triazoles and the preparation of new triazole‐functionalized biologically active molecules using classical approaches, and focuses on the contributions of the Ferreira's group throughout the last decades.